PTH-018 Results on the national uptake of the JETS e-Portfolio. (23rd September 2015) - Mehta, T; Dowler, K; McKaig, B; Valori, R; Dunckley, P
Abstract : Introduction: Following a successful pilot, JAG released their new JETS e-Portfolio in September 2009. The JETS e-Portfolio has been designed to support trainees in endoscopy by providing them with a web-based, electronic tool for logging their endoscopic experience. It allows trainees to demonstrate their competence levels, develop a personal development plan and complete JAG DOPS forms. The JETS e-Portfolio has been designed to support and streamline the JAG trainee certification process which is currently under review. Methods: The JETS e-Portfolio was released nationally in early September 2009. Initially it was released on a Deanery-by-Deanery basis starting in the Severn and West Midlands regions. It can now be used by any trust in any Deanery. Here we present the current uptake data at the time of writing. Results: Since September 2009, 34 trusts (22.5%) in England have starting using the JETS e-Portfolio. 112 trainees now use the e-Portfolio to log their endoscopic experience. 1096 endoscopy lists have been logged with 5116 procedures added. 412 JAG approved DOPS have also been added to the system. There have been no major IT issues and the feedback from trainees using the system has been excellent. Conclusion: After 3 months of release, nearly one quarter of English Trusts are using the JETS e-Portfolio. A staged release in Wales and Northern Ireland is also planned. Initial data suggest that trainees are very willing to input data into the JETS e-Portfolio. The e-Portfolio also appears to be supporting the training process through the regular use of DOPS forms. Details on how to set up the JETS e-Portfolio are available on the JAG website.